GAME CENTER: WAHANA PERMAINAN BERBASIS TRADISIONAL DAN DIGITAL - Wahyuni, Sari; Alhamdani, M Ridha; Putro, Jawas Dwijo (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2021)
Over time, everyone grows up with what he remembers during our lifetime. Game Center is the place for the memory gathering. This has an impact on the interest of both young and old players which will continue to grow every year. Currently Pontianak does not have this game center. Meanwhile, game enthusiasts, especially in terms of audio-visual, are getting higher. From the static data in Statista, it states that the high demand and activity from games. Therefore, it is necessary to design a Game Center. The Game Center design is designed not only as a mere function of a game center, but also as a place for traditional games of the local community as well as a communal space that fills social activities. This game center design is done by analyzing internal and external sources and literature as well as standard references in existing game centers. The space requirements of the actors' activities also need to be analyzed to find the spatial program in the game center. Function, layout, circulation and utility are prioritized to produce a Game Center with communal functions. The building is designed to have three separate building masses. One mass building in the middle as the main building with a central function. The other two masses of the building are placed around the main building.